A series of d10 metal coordination polymers based on a flexible bis(2-methylbenzimidazole) ligand and different carboxylates: synthesis, structures, photoluminescence and catalytic properties1. Issue 11 (21st March 2015) - Hao, Jin-ming; Yu, Bao-yi; Van Hecke, Kristof; Cui, Guang-hua
<x xml:space="preserve">Abstract</x> Six d10 metal coordination polymers have been prepared and characterized. Complexes possess structural diversities with interesting topologies and high catalytic activities for the degradation of methyl orange.